2013
DOI: 10.1039/c3ob41251b
|View full text |Cite
|
Sign up to set email alerts
|

An approach to hyperolactone C and analogues using late stage conjugate addition on an oxonium ylide-derived spirofuranone

Abstract: A stereocontrolled synthesis of norphenyl hyperolactone C together with its utility as a direct precursor to the anti-HIV agent hyperolactone C and analogues by addition of organolithiums, are described. Preliminary studies to access this key building block in a catalytic enantioselective manner are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The enhanced rate of enamides and vinyl sulfides relative to allylic amides and sulfides, , for example, further illustrates the role of oxidation potential on the activation barrier. The disparate reactivities of enolsilanes in carbocycles, where nucleophilic addition occurs, and heterocycles, where C–H bond cleavage dominates, , illustrate the importance of cation stability on the reaction pathway. The facile oxidation of transiently generated enamines to form α,β-unsaturated iminium ions demonstrates the role of both factors.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced rate of enamides and vinyl sulfides relative to allylic amides and sulfides, , for example, further illustrates the role of oxidation potential on the activation barrier. The disparate reactivities of enolsilanes in carbocycles, where nucleophilic addition occurs, and heterocycles, where C–H bond cleavage dominates, , illustrate the importance of cation stability on the reaction pathway. The facile oxidation of transiently generated enamines to form α,β-unsaturated iminium ions demonstrates the role of both factors.…”
Section: Resultsmentioning
confidence: 99%
“…Following precedent on a closely related system ( 8b with R 3 = H) in our recent synthesis of hyperolactone C ( 4 ), a phenyl group was introduced into dimethylated spirofuranone 8b by conjugate addition–oxidation, giving spirofuranone 8d in 78% yield (Scheme ). Alternatively, as mentioned in the Introduction, the phenyl group could, in principle, be present prior to the ylide chemistry.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hyperolactone C ( 4 ) forms part of a small family of related lactones, originally isolated from the leaves and stems of Hypericum chinese L . It is an attractive target for fundamental and structure–activity relationship synthetic studies, due to a combination of structural complexity and potential as a lead in anti-HIV research. , We have previously reported approaches to hyperolactone C ( 4 ) using tandem oxonium ylide formation–[2,3]-sigmatropic rearrangements ( 1 → 3 , Scheme , R′ = Ph or H, R′′ = alkyl). However, our earlier studies did not fully control the relative stereochemistry and required post-rearrangement oxidation to introduce the furanone double bond. The present work sought to address both of these latter issues, by constraining the allylic ether as part of a cyclic unsaturated acetal 5 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence was completed by protodesilylation with p-TsOH·H 2 O to deliver the spiroacetal 6 in 78 % yield upon isolated with 91 % ee. The oxygen atom in the ring appears to be essential for promoting rapid oxidation in consideration of the studies from Guo and Mayr, [11] who showed that carbocyclic enolsilanes add to DDQ rather than form enones.…”
mentioning
confidence: 99%